2004
DOI: 10.1128/jvi.78.12.6459-6468.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Protein VII Condenses DNA, Represses Transcription, and Associates with Transcriptional Activator E1A

Abstract: Adenovirus protein VII is the major protein component of the viral nucleoprotein core. It is highly basic, and an estimated 1070 copies associate with each viral genome, forming a tightly condensed DNA-protein complex. We have investigated DNA condensation, transcriptional repression, and specific protein binding by protein VII. Xenopus oocytes were microinjected with mRNA encoding HA-tagged protein VII and prepared for visualization of lampbrush chromosomes. Immunostaining revealed that protein VII associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 62 publications
3
86
0
Order By: Relevance
“…Protein VII is the major protein component of the core with an estimated 1,070 copies present per virion (9) and is primarily responsible for establishing viral chromatin structure. It can potently condense DNA in vitro and in vivo and also repress transcription (3,6,21,35). This is consistent with the highly condensed configuration of viral chromatin found within the virion.…”
supporting
confidence: 75%
See 4 more Smart Citations
“…Protein VII is the major protein component of the core with an estimated 1,070 copies present per virion (9) and is primarily responsible for establishing viral chromatin structure. It can potently condense DNA in vitro and in vivo and also repress transcription (3,6,21,35). This is consistent with the highly condensed configuration of viral chromatin found within the virion.…”
supporting
confidence: 75%
“…We and others have reported that protein VII from infectious viral particles enters the cell along with viral DNA (8,15,18,21). We wanted to examine the appearance of this input protein VII and also the new production of pre-protein VII and mature protein VII during infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations